2017
DOI: 10.1093/mnras/stx1466
|View full text |Cite
|
Sign up to set email alerts
|

Galaxy and Mass Assembly (GAMA): halo formation times and halo assembly bias on the cosmic web

Abstract: We present evidence for halo assembly bias as a function of geometric environment. By classifying GAMA galaxy groups as residing in voids, sheets, filaments or knots using a tidal tensor method, we find that low-mass haloes that reside in knots are older than haloes of the same mass that reside in voids. This result provides direct support to theories that link strong halo tidal interactions with halo assembly times. The trend with geometric environment is reversed at large halo mass, with haloes in knots bein… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 89 publications
4
42
0
Order By: Relevance
“…The trend persists for all halo masses, but with a significantly larger scatter of halo ages at the high-mass end, as the formation redshifts also progressively become more recent, as expected. A similar trend with halo formation time has already been measured in SAMs (Wang et al 2013a;Tojeiro et al 2017) and also for galaxies in the EAGLE hydrodynamical simulation (Matthee et al 2017). It likely arises because central galaxies in early-formed halos have more time for accretion and star formation and thus end up being more massive.…”
Section: The Stellar Mass-halo Mass Relationsupporting
confidence: 79%
See 1 more Smart Citation
“…The trend persists for all halo masses, but with a significantly larger scatter of halo ages at the high-mass end, as the formation redshifts also progressively become more recent, as expected. A similar trend with halo formation time has already been measured in SAMs (Wang et al 2013a;Tojeiro et al 2017) and also for galaxies in the EAGLE hydrodynamical simulation (Matthee et al 2017). It likely arises because central galaxies in early-formed halos have more time for accretion and star formation and thus end up being more massive.…”
Section: The Stellar Mass-halo Mass Relationsupporting
confidence: 79%
“…Observational studies of assembly bias have generally produced mixed results. There have been several suggestive detections in observations (Berlind et al 2006;Yang et al 2006;Tinker et al 2008bTinker et al , 2017bWang et al 2008Wang et al , 2013bCooper et al 2010;Lacerna et al 2014a;Hearin et al 2015;Watson et al 2015;Miyatake et al 2016;Saito et al 2016;Zentner et al 2016;Montero-Dorta et al 2017;Tojeiro et al 2017), while numerous other studies indicate the impact of assembly bias to be small (Abbas & Sheth 2006;Blanton & Berlind 2007;Croton & Farrar 2008;Tinker et al 2008aTinker et al , 2011Deason et al 2013;Lacerna et al 2014b;Lin et al 2016;Vakili & Hahn 2016;Dvornik et al 2017). The situation is further complicated as various systematic effects can mimic the effects of assembly bias (e.g., Campbell et al 2015;Busch & White 2017;Lacerna et al 2017;Sin et al 2017;Tinker et al 2017a;Zu & Mandelbaum 2017) and the evidence for assembly bias to date remains inconclusive and controversial.…”
Section: Introductionmentioning
confidence: 96%
“…Semi-analytic and hydrodynamical simulations have since confirmed a correlation between halo assembly time and the stellar to halo mass ratio, and have shown how halo formation time partly explains the scatter in the stellar mass to halo mass relation (e.g. Matthee et al 2017;Tojeiro et al 2017;Zehavi et al 2018). Observationally, Tojeiro et al (2017) show that the stellar to halo mass ratio of central galaxies varied with position within the cosmic web, at fixed halo mass.…”
Section: Stellar To Halo Mass Ratiomentioning
confidence: 97%
“…Early studies, however, have demonstrated observations of halo assembly bias. For example, Tojeiro et al (2017) compare a halo age proxy with respect to large-scale tidal environment defined in the Galaxy And Mass Assembly (GAMA; Driver et al 2009Driver et al , 2011 survey. They quantify tidal strength using the geometric classification of Eardley et al (2015) to characterise regions into geometric voids, sheets, filaments and knots corresponding to zero, one, two and three dimensions of collapse respectively.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that there is no significant influence of the cosmic web on galaxy luminosity functions. Using the same sets of data, a recent study by Tojeiro et al (2016) indicates that low mass halos in clusters are older than halos of similar mass in voids. However, the trend is reversed for high mass halos, with halos in clusters being younger than halos in voids.…”
Section: Introductionmentioning
confidence: 99%